IMPLEMENTASI SINGLE STAGE REDUCER-BUCK CONVERTER PADA MOBIL LISTRIK DUA PENUMPANG - Gigih Prabowo; Era Purwanto; Syechu Dwitya Nugraha; Fifi Hesty Sholihah; Ony Asrarul Qudsi, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The research focuses on the development of Low-Cost Green Car (LCGC) and zero emission vehicle concepts in several countries as a response to declining oil reserves and environmental pollution concerns. Context of electric vehicles adopting these concepts, electric motors have become the primary and only viable choice, even though innovations in electric motor control often considered expensive. This research aims to develop an economical electric motor control system using a 60V/10kW DC motor with a 12V input voltage and control by an STM32F407 Microcontroller that generates PWM signals. It is equipped with a 20x4 LCD for monitoring current and output voltage. The control system involves a basic switching motor driver that sends PWM signals from the microcontroller to the IGBT driver 2SP0115T, including two operating modes (forward and reverse) controlled through the gearbox and throttle pedal. The system also includes a 60 to 12.5V Reducer DC-DC Buck converter as a power source for accessory features in the electric vehicle, such as the speedometer, headlights, taillights, turn signals, horn, and power windows. With this implementation, a compact electric vehicle has been successfully created that utilizes a DC motor with a Reducer DC-DC Buck converter all powered by a single battery source